Polydopamine layered poly (ether imide) ultrafiltration membranes tailored with silver nanoparticles designed for better permeability, selectivity and antifouling - Saraswathi, Meenakshi Sundaram Sri Abirami; Rana, Dipak; Alwarappan, Subbiah; Gowrishankar, Shanmugaraj; Vijayakumar, Prabu; Nagendran, Alagumalai (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] •Bio-inspired polydopamine coated PEI membranes are fabricated efficiently.•Successful in situ immobilization of AgNPs in PEI/PD membranes.•PEI/PD/Ag membranes displayed enhanced hydrophilicity and BSA/HA/Oil rejection.•PEI/PD/Ag membranes showed excellent anti-organic fouling and anti-biofouling.•PEI/PD/Ag membranes are promising for prospective use in the water treatment. Poly (ether imide) [PEI] ultrafiltration membranes are coated by polydopamine (PD) and immobilized with silver nanoparticles (AgNPs) to improve the permeation, contaminant separation and anti-fouling properties. The tailored membranes displayed enhanced permeability (97.2 Lm−2 h−1), hydraulic resistance (13.8 kPa/Lm−2 h−1), average roughness (43 nm), contaminant rejection (>97%) with a higher flux recovery ratio (>95%). PEI/PD/Ag membranes showed anti-biofouling property against gram negative and gram positive bacteria and facilitated the separation of toxic contaminants. The outstanding stability of PD coating and the presence of AgNPs offer effective and safe water separation.